2008
DOI: 10.1097/fjc.0b013e31818a8927
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate and Pioglitazone Do Not Ameliorate the Altered Vascular Reactivity in Aorta of Isoproterenol-treated Rats

Abstract: Chronic stimulation of beta-adrenoceptors with isoproterenol induces alteration of vascular reactivity and increases local pro-inflammatory cytokines. We investigated whether fenofibrate and pioglitazone, PPAR-alpha and -gamma agonists, respectively, improve the changes in vascular reactivity induced by isoproterenol. Wistar rats received isoproterenol (0.3 mg x kg x day, SC) or vehicle (CT) plus fenofibrate (alpha, 100 mg x kg x day, PO), pioglitazone (gamma, 2.5 mg.kg.day, PO), or water for 7 days. In aortas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
2
4
0
2
Order By: Relevance
“…Together, these results reinforce our previous studies [7], [8], [26], suggesting that ISO treatment induces changes in vascular reactivity to phenylephrine that are associated with oxidative stress. Furthermore, we add new data that these adjustments seem to be dependent of the presence of functional vascular β 2 -AR.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Together, these results reinforce our previous studies [7], [8], [26], suggesting that ISO treatment induces changes in vascular reactivity to phenylephrine that are associated with oxidative stress. Furthermore, we add new data that these adjustments seem to be dependent of the presence of functional vascular β 2 -AR.…”
Section: Resultssupporting
confidence: 91%
“…However, little is known about the mechanisms associated with the effects of long-term β-AR activation in vascular cells. Previous studies suggested that ISO-induced β-AR overactivation leads to alterations in vascular tone depending on the vessel type [8], [9], [26], [29], [30]. In murine aortas, ISO treatment enhances the contractile response to the α 1 -adrenoceptor agonist phenylephrine and is associated with elevated ROS generation and impaired NO bioavailability [8], [30].…”
Section: Discussionmentioning
confidence: 98%
“…In MRA from SHR, pioglitazone treatment slightly improved the impaired ACh‐induced vasodilatation. Moreover, the phenylephrine contraction was similar in MRA from WKY and SHR, and remained unmodified after pioglitazone treatment; this result, which agrees with that found in isoprenaline‐treated rats (Fukuda et al ., 2008), apparently excludes an effect of the glitazone on vasoconstrictor responses.…”
Section: Discussionsupporting
confidence: 89%
“…The administration of isoproterenol, a non-selective β-adrenoceptor agonist, to laboratory animals for several days is used as a model of prolonged β-adrenoceptor stimulation. In the vasculature of these animals, we demonstrated that isoproterenol treatment increases the vasoconstrictor response to the α 1 -adrenoceptor agonist phenylephrine as well as to the serotonin (5-HT) agonist in rat (31) and mouse ( Figure 3A) aorta, although no changes in acetylcholine-induced relaxation were observed (31,32). In addition, endothelial removal and L-NAME incubation normalized the hyperreactivity to phenylephrine observed in aortas from isoproterenol-treated rats, indicating that persistent activation of β-adrenoceptors impairs basal endothelial-derived NO (31,32).…”
Section: Endothelial Dysfunction and Sympathetic Hyperactivitymentioning
confidence: 99%